Expression, purification, crystallization and preliminary X‐ray analysis of the receiver domain of Staphylococcus aureus LytR protein. Issue 12 (1st December 2013) - Shala, Agnesa; Patel, Kevin H.; Golemi‐Kotra, Dasantila; Audette, Gerald F.
<x xml:space="preserve">Abstract</x> The response‐regulatory protein LytR belongs to a family of transcription factors involved in the regulation of important virulence factors in pathogenic bacteria. The protein consists of a receiver domain and an effector domain, which play an important role in controlled cell death and lysis. The LytR receiver domain (LytRN) has been overexpressed, purified and crystallized using the sitting‐drop and hanging‐drop vapour‐diffusion methods. The crystals grew as needles, with unit‐cell parameters a = b = 84.82, c = 157.3 Å, α = β = 90, γ = 120°. LytRN crystallized in space group P6122 and the crystals diffracted to a maximum resolution of 2.34 Å. Based on the Matthews coefficient (VM = 5.44 Å3 Da−1), one molecule is estimated to be present in the asymmetric unit.